2017
DOI: 10.9734/arjass/2017/33363
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Spending and Economic Growth in Nigeria: In Search of a Stable Relationship

Abstract: In this study, recent development in government expenditure and epistemological literatures on the relationship between public spending and economic growth in Nigeria are examined. The primary aim of this paper is to explore the relationship between government expenditure and economic growth with the view to establishing a stable relationship. In view of that, an ARDL model is employed to provide the framework for estimating the existence or otherwise of the equilibrium relationship among the examined variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Wang et al (2018), Wang et al, (2019), and Szczygielski et al, 2017 argue that public sector investment is an important ingredient for private sector investment. Nevertheless, non-infrastructural public investment would crowd out the level of private sector involvement in economic development (Geddes et al, 2017;Idris & Bakar, 2017). Studies by Valadkhani (2004) and Khan & Rinluhart (1990), singled out factors such as GDP growth rate, household level of income, the balance of payment and inflation rate as key determinants of private sector investment.…”
Section: Foreign Remittances and Private Sector Investmentmentioning
confidence: 99%
“…Wang et al (2018), Wang et al, (2019), and Szczygielski et al, 2017 argue that public sector investment is an important ingredient for private sector investment. Nevertheless, non-infrastructural public investment would crowd out the level of private sector involvement in economic development (Geddes et al, 2017;Idris & Bakar, 2017). Studies by Valadkhani (2004) and Khan & Rinluhart (1990), singled out factors such as GDP growth rate, household level of income, the balance of payment and inflation rate as key determinants of private sector investment.…”
Section: Foreign Remittances and Private Sector Investmentmentioning
confidence: 99%
“…A related study by [16] indicated that government spending on transport and communication, education and health infrastructure has significant effects on economic growth; whereas spending on agriculture and natural resources infrastructure recorded a significant inverse effect on economic growth in Nigeria. Chijioke and Amadi [49] concurred with [16], while [29] revealed that positive and significant relationship exists between public sector spending and economic growth in Nigeria based on an ARDL model. A study by [58] found that an increase in capital expenditure causes a positive influence on the Nigerian economy which can be optimised through investment in rural roads and electricity.…”
Section: Theoretical Framework and Empirical Reviewmentioning
confidence: 86%
“…The veracity of contradictory results on whether economic construction sector public investment increases economic growth in Nigeria raises more concerns and thus, requires further empirical investigation. Giang and Pheng [28] and Idris and Bakar [29] agree that the relationship between construction sector and economic growth appears more complicated than thought.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the economy witnessed various hurdles which affected the aggregate economic activities in addition to the devastating effects of world oil prices. This scenario has resulted to structural imbalances thereby affecting the country's revenue mobilisation capacity, large and inefficient public sector, inadequate savings and investment capacity as well as persistent large fiscal deficits [1].…”
Section: Introductionmentioning
confidence: 99%